The impact of artificial intelligence on decision-making in Venture Capital Firms - Schmidt, Christina Maria (2020)
This exploratory study examines the opportunity of Artificial Intelligence in the decision-making process of Venture Capitals. Investors have to take decisions under uncertainty, time pressure and suffer from bias. This study investigates the potential of Artificial Intelligence to overcome these challenges and improve the process. The results are based on a qualitative analysis based on 12 interviews with Venture Capitals, AI Experts, and companies offering solutions for Venture Capitals as well as secondary data in form of academic articles and online magazines. The findings reveal that Artificial Intelligence is currently mostly implemented at the beginning of the decision-making process. The usage of Artificial Intelligence improves the process of making decisions by lowering uncertainty, bias and increasing productivity and efficiency. The interviews show that that AI can be implemented in every step in the decision-making process and presents the specific use cases. Furthermore, implementation challenges and implications for practice are outlined. By applying AI, Venture Capitals improve their decision-making process, which ultimately could have a positive impact on the return of their portfolio.